Pengaruh Perlakuan Akuntansi Murabahah Terhadap Kepercayaan Nasabah - Misjelina Br Surbakti; Arriza Khana; Mujib Al Fathan; Arey Slaiman; Sob Ey Soppry; Muammar Khadapi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Murabahah accounting is important for keeping things clear and responsible in Islamic financial institutions. Using murabahah accounting as required by PSAK 102, especially when it comes to how transactions are recorded, measured, shown, and shared, can affect how much customers trust the institution. This article looks at how the way murabahah accounting is handled influences customer trust, based on research from national and international academic sources. The study uses a literature review to look at past work on how murabahah accounting is used, how well it follows Islamic accounting rules, and what factors affect customer trust. The results show that when murabahah accounting is done clearly and consistently according to PSAK 102, it helps build customer trust. Being open about the cost of the item, the profit added, and how payments are made is a big part of making customers feel confident in Islamic financial services. So, murabahah accounting does more than just keep track of money—it also helps build trust and make Islamic financial institutions last longer.